2018
DOI: 10.1111/tpj.14028
|View full text |Cite
|
Sign up to set email alerts
|

The multistress‐induced Translocator protein (TSPO) differentially modulates storage lipids metabolism in seeds and seedlings

Abstract: Translocator proteins (TSPO) are conserved membrane proteins extensively studied in mammals, but their function is still unclear. Angiosperm TSPO are transiently induced by abiotic stresses in vegetative tissues. We showed previously that constitutive expression of the Arabidopsis TSPO (AtTSPO) could be detrimental to the cell. Degradation of AtTSPO requires an active autophagy pathway. We show here that genetic modifications of TSPO expression in plant and yeast cells reduce the levels of cytoplasmic lipid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Given that sku5 shows alterations of ABA signaling pathways in spaceflight (Figure 13), it can be hypothesized that the lack of SKU5 may affect the function of these nanodomain-localized ABA signaling processes under stress conditions. The expression of a chloroplastic aldehyde reductase, ChlADR (AT1G54870), involved in the detoxification of reactive carbonyls formed as a result of lipid peroxidation, and TSPO, which participates in mobilization of lipids, are induced by stress and highly induced in the spaceflight acclimation of sku5 (Guillaumot et al, 2009;Yamauchi et al, 2011;Jurkiewicz et al, 2018). These patterns match the gene expression trends of the spaceflight-induced LEA family genes that are thought to directly participate in membrane stabilization under stress (Battaglia et al, 2008;Hundertmark and Hincha, 2008;Candat et al, 2014).…”
Section: Sku5 Mutation Produces a Dramatic Increase In Differential Gmentioning
confidence: 61%
“…Given that sku5 shows alterations of ABA signaling pathways in spaceflight (Figure 13), it can be hypothesized that the lack of SKU5 may affect the function of these nanodomain-localized ABA signaling processes under stress conditions. The expression of a chloroplastic aldehyde reductase, ChlADR (AT1G54870), involved in the detoxification of reactive carbonyls formed as a result of lipid peroxidation, and TSPO, which participates in mobilization of lipids, are induced by stress and highly induced in the spaceflight acclimation of sku5 (Guillaumot et al, 2009;Yamauchi et al, 2011;Jurkiewicz et al, 2018). These patterns match the gene expression trends of the spaceflight-induced LEA family genes that are thought to directly participate in membrane stabilization under stress (Battaglia et al, 2008;Hundertmark and Hincha, 2008;Candat et al, 2014).…”
Section: Sku5 Mutation Produces a Dramatic Increase In Differential Gmentioning
confidence: 61%
“…The C-terminal region of LEA4-5 is responsible for its antioxidant activity and in the scavenging of metal ions under stress conditions, whereas the N-terminal can function as a chaperone in the folding of enzyme proteins and in preventing their unfolding that results in protection of the enzyme activity [19,30]. TSPO, belonging to the Trp-rich sensory protein/peripheral-type benzodiazepine receptor group protein, interacts with and regulates PIP2;7, a plasma membrane aquaporin, in the endoplasmic reticulum and Golgi membrane during abiotic stress conditions [20,21]. The interaction between TSPO and PIP2;7 triggers the reduction of PIP2;7 channels present in the plasma membrane and reduces the water transport activity [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…TSPO, belonging to the Trp-rich sensory protein/peripheral-type benzodiazepine receptor group protein, interacts with and regulates PIP2;7, a plasma membrane aquaporin, in the endoplasmic reticulum and Golgi membrane during abiotic stress conditions [20,21]. The interaction between TSPO and PIP2;7 triggers the reduction of PIP2;7 channels present in the plasma membrane and reduces the water transport activity [20,21]. ABR is a Ser/Thr kinase and interacts with phospholipase D-derived phosphatidic acid (PA) [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, however, TSPO has been primarily reported to be a monomer. A monomer form of 18–22 kDa was found in Arabidopsis thaliana in a variety of tissues (Lindemann et al 2004 ; Guillaumot et al 2009a ; Hachez et al 2014 ; Jurkiewicz et al 2018 , 2020 ), although an early paper showed the presence of a possible dimer in potato (Corsi et al 2004 ) and monomer and potential dimer forms were detected in Digitalis lanata cell cultures (Lindemann et al 2004 ). More experimentation will be necessary to establish the potential for formation and functional significance of oligomeric forms in plants and other species.…”
Section: Tspo Structure and Locationmentioning
confidence: 99%